Does cognitive load moderate students’ learning engagement mechanism in blended learning? - Zidi, Chen; Jalaludin, Nur Atiqah; Rasul, Mohamad Sattar (Institute of Advanced Engineering and Science, 2025)
With the popularity of technology-supported blended learning (BL) in vocational colleges, students’ cognitive load (CL) caused by the increasing complexity of BL environments potentially impact the overall learning satisfaction (LS). In order to explore the effects of CL on students’ BL, this study investigates how different dimensions of learning engagement (LE) (emotional, cognitive, and behavioral) impact on students’ LS and whether CL can moderate these relationships. This quantitative study was conducted among 615 Chinese vocational students. Survey research was carried out by questionnaires that have been well-established that were taken and modified from previous studies. Structural equation modeling (SEM) was used to analyze the relationships among these variables. Findings revealed that emotional, cognitive, and behavioral engagement (BE) can positively predict LS. Additionally, BE mediates the relationship between psychological engagement (emotional and cognitive) and LS when CL is not at a low level. CL moderates the pathways from psychological engagement to BE and in turn changes the LE influence mechanism on LS. This study provides valuable insights for educators to stimulate students’ engagement by satisfying their psychological needs, and optimize teaching design to balance CL in order to maintain active LE and satisfaction levels.